Medicarpin suppresses lung cancer cell growth in vitro and in vivo by inducing cell apoptosis - Shen Zongyi; Yin Liqi; Chang Manxia; Wang Haifeng; Hao Mingxuan; Liang Youfeng; Guo Rui; Bi Ying; Wang Jiansong; Yu Changyuan; Li Jinmei; Zhai Qiongli; et al. (Acta Pharmaceutica)
Lung cancer (LC) is the leading cause of cancer deaths worldwide. Surgery, chemoradiotherapy, targeted therapy, and immunotherapy are considered dominant treatment strategies for LC in the clinic. However, drug resistance and meta-stasis are two major challenges in cancer therapies. Medicarpin (MED) is an isoflavone compound isolated from alfalfa, which is usually used in traditional medicine. This study was de sig ned to evaluate the anti-LC effect and reveal the underlying mechanisms of MED in vivo and in vitro. We found that MED could significantly inhibit proliferation, induce apoptosis, and cell cycle arrest of A549 and H157 cell lines. Basically, MED induced cell apoptosis of LC cells by upregu lating the expression of pro-apoptotic proteins BAX and Bak1, leading to the cleavage of caspase-3 (Casp3). Moreover, MED inhibited the proliferation of LC cells via downregulating the expression of proliferative protein Bid. Overall, MED inhibited LC cell growth in vitro and in vivo via suppressing cell proliferation and inducing cell apoptosis, suggesting the therapeutic potential of MED in treating LC.